Pengaruh Strategi Pembelajaran Student-Centered Learning dan Kemampuan Spasial terhadap Kreativitas Mahasiswa - Aan Ardian; Sudji Munadi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2015)
This study aims at investigating the difference of creativity between the students treated with the Student-Centered Learning (SCL) strategy and the students treated with the Direct Learning strategy. It was a quasi-experimental study employing the non-equivalent control group design. It was conducted using the 2x2 factorial design. The research population were 40 students attending the course of Fabrication Construction Design. The results of the study showed that (1) The creativity of the students using the SCL strategy attained mean scores of 42.65, higher than the students using the Direct Learning strategy with mean scores of 39. (2) The students with high spatial ability using the SCL strategy attained mean scores of 49, higher than the students using the Direct Learning strategy with mean scores of 36.3. (3) The students with low spatial ability using the SCL strategy attained mean scores of 36.3, lower than the students using the Direct Learning strategy with mean scores of 41.70. (4) There was an interaction between the learning strategy and the spatial ability in terms of the effect on the creativity.